Overview on Derivatives Trade in China - Tianying Zhou (European Scientific Journal, ESJ, 2016)
Since 1980s, derivatives market has become the significant component of international financial market, and its founding and development contributes to the characteristics of modern financial market. Derivatives, which have gone through the stages of massive import, fast growth and gradual maturity, are one of the fruits of financial creations. It has also led to constructive reform of financial system. As for present market, according to BIS, the notional principle of exchange traded derivatives and options sums to 73.46 trillion US dollars. While the notional value of contract of global OTC derivatives is 691 trillion US dollars, the add-up would be 764.46 trillion US dollars. The OTC derivatives take up 90.39% global derivatives market. In the meanwhile, according to ISDA statistics, 94% of global 500 companies trade in OTC derivatives market.